2009
DOI: 10.1002/jpln.200700087
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic approach to assess trace–heavy metal contents in contaminated floodplain soils via spectrally active soil components

Abstract: Soil samples from grassland plots in the Hase floodplain near Osnabrück (NW Germany) were analyzed using visible and near‐infrared laboratory spectroscopy (VNIRS) by means of an ASD FieldSpec II Pro FR‐ spectroradiometer (spectral range 0.4–2.5 µm), paralleled by atomic‐absorption spectrometry (AAS), automated combustion for Corg quantification, and texture analysis. By AAS, contents of Cu, Zn, and Pb were found to be clearly elevated which is due to industrial effluents into the river in the 19th and 20th cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 29 publications
2
28
0
2
Order By: Relevance
“…Contradictory conclusions on the major absorption feature mechanisms that can enable i n d i r e c t p r e d i c t i o n o f h e a v y m e t a l s w e r e presented by the abovementioned studies. However, their results cannot be generalized, as soil properties (e.g., soil C org content) were distinctly different in the different studies (Vohland et al 2009). Vohland et al (2009) used soil samples taken from grassland plots that showed a very wide range of both C org (0.37%-9.24%) and clay contents (0%-37.8%), with the aim of investigating whether the heavy metal contents of these samples can actually be assessed by NIRS.…”
Section: Reflectance Spectroscopy Of Heavy Metalsmentioning
confidence: 94%
See 2 more Smart Citations
“…Contradictory conclusions on the major absorption feature mechanisms that can enable i n d i r e c t p r e d i c t i o n o f h e a v y m e t a l s w e r e presented by the abovementioned studies. However, their results cannot be generalized, as soil properties (e.g., soil C org content) were distinctly different in the different studies (Vohland et al 2009). Vohland et al (2009) used soil samples taken from grassland plots that showed a very wide range of both C org (0.37%-9.24%) and clay contents (0%-37.8%), with the aim of investigating whether the heavy metal contents of these samples can actually be assessed by NIRS.…”
Section: Reflectance Spectroscopy Of Heavy Metalsmentioning
confidence: 94%
“…However, their results cannot be generalized, as soil properties (e.g., soil C org content) were distinctly different in the different studies (Vohland et al 2009). Vohland et al (2009) used soil samples taken from grassland plots that showed a very wide range of both C org (0.37%-9.24%) and clay contents (0%-37.8%), with the aim of investigating whether the heavy metal contents of these samples can actually be assessed by NIRS. In addition, they explored statistically whether a valid prediction mechanism can be identified.…”
Section: Reflectance Spectroscopy Of Heavy Metalsmentioning
confidence: 94%
See 1 more Smart Citation
“…In order to examine the relationship between the spectra from soil samples with different pretreatments at each single wavelength, the reflectance of the soil samples was measured from soil samples with and without the air-drying, grinding and 2-mm sieving pretreatment [13,31].…”
Section: Laboratory Vnir Reflectance Analysesmentioning
confidence: 99%
“…Compared to conventional laboratory analysis, VNIRS is accepted as rapid and potentially cost-effective method. Additionally, it can be applied in the field by portable spectrometers [4]. Field spectroscopy has an important role in environmental science in which it allows to characterize the object being observed with in situ measurements [5].…”
Section: Introductionmentioning
confidence: 99%